Effect of an Aerobic Exercise Program and Gymnema Supplementation on Plasma Ghrelin Levels and Sweet Taste Preference in Obese Women - Azadi, Roya; Irandoust, Khadijeh; Taheri, Morteza (Health Nexus, 2025)
Obesity is associated with dysregulation of appetite control and a preference for sweet taste. Ghrelin is recognized as a key hormone in appetite stimulation and sweet taste preference. The aim of this study was to examine the effect of aerobic exercise and Gymnema supplementation on plasma ghrelin levels and sweet taste preference in obese women. In this quasi-experimental study, 45 obese women aged 20 to 45 were randomly assigned into three groups: aerobic training, aerobic training plus Gymnema supplementation, and a control group (15 participants per group). The intervention groups engaged in aerobic exercise for 8 weeks. The second group additionally received 400 mg of Gymnema supplement daily. Plasma ghrelin levels were measured using the ELISA method, and sweet taste preference was assessed via a questionnaire. Post-intervention, plasma ghrelin levels significantly increased in both the aerobic and combined intervention groups (P < 0.001), while no change was observed in the control group. The intensity and frequency of sweet cravings significantly decreased in both intervention groups (P < 0.001), although no significant difference was found between the two. Furthermore, anthropometric indices including weight, waist-to-hip ratio (WHR), and body mass index (BMI) were significantly reduced in the intervention groups. Aerobic exercise, whether alone or combined with Gymnema supplementation, can contribute to modulating ghrelin levels, reducing sweet cravings, and improving body composition in obese women. Gymnema supplementation may be considered a complementary strategy for managing unhealthy eating behaviors.